Ruminal biohydrogenation and abomasal flow of fatty acids in lactating cows fed diets supplemented with soybean oil, whole soybeans, or calcium salts of fatty acids - Freitas, J. E.; Takiya, C. S.; Del Valle, T. A.; Barletta, R. V.; Venturelli, B. C.; Vendramini, T. H. A.; Mingoti, R. D.; Calomeni, G. D.; Gardinal, R.; Gandra, J. R.; Bettero, V. P. [UNESP]; Ferreira de Jesus, E. [UNESP]; et al. (Elsevier B.V., 2018)
Ruminants have a unique metabolism and digestion of unsaturated fatty acids (UFA). Unlike monogastric animals, the fatty acid (FA) profile ingested by ruminants is not the same as that reaching the small intestine. The objective of this study was to evaluate whole raw soybeans (WS) in diets as a replacer for calcium salts of fatty acids (CSFA) in terms of UFA profile in the abomasal digesta of early- to mid-lactation cows. Eight Holstein cows (80 +/- 20 d in milk, 22.9 +/- 0.69 kg/d of milk yield, and 580 +/- 20 kg of body weight; mean I. standard deviation) with ruminal and abomasal cannulas were used in a 4 x 4 Latin square experiment with 22-d periods. The experiment evaluated different fat sources rich in linoleic acid on ruminal kinetics, ruminal fermentation, FA abomasal flow, and milk FA profile of cows assigned to treatment sequences containing a control (CON), with no fat source; soybean oil, added at 2.68% of diet dry matter (DM); WS, addition of WS at 14.3% of diet DM; and CSFA, addition of CSFA at 2.68% of diet DM. Dietary fat supplementation had no effect on nutrient intake and digestibility, with the exception of ether extract. Cows fed fat sources tended to have lower milk fat concentration than those fed CONT. In general, diets containing fat sources tended to decrease ruminal neutral detergent fiber digestibility in relation to CON. Cows fed WS had lower ruminal digestibility of DM and higher abomasal flow of DM in comparison to cows fed CSFA. As expected, diets containing fat supplements increased FA abomasal flow of C18:0 and total FA. Cows fed WS tended to present a higher concentration of UFA in milk when compared with those fed CSFA.. This study suggests that under some circumstances, abomasal flow of UFA in early lactation cows can be increased by supplementing their diet with fat supplements rich in linoleic acid, regardless of rumen protection, with small effects on ruminal DM digestibility.
Keywords: fat source; linoleic acid; milk fatty acid profile; ruminal digestibility